Quality Evaluation Criteria for Consumer Electrical/Electronic Products: A Qualitative Study - Çavdar, Ertuğrul; Yildiz, Bülent (Alanya Alaaddin Keykubat Üniversitesi, 2022)
The main purpose of this study is to determine the factors that determine the quality perception of customers in electrical and electronic consumer products directly from their own speeches. For this purpose, the participants were asked to write down why they thought the products they used were of good quality and why they were of poor quality. In the study, in which the survey data of 191 participants were evaluated, the data were analyzed in the MAXQDA 2022 program. In the coding of participant statements as a quality dimension, the dimensions in the literature were primarily taken into consideration, and sub-codings were also included under the quality dimensions when deemed necessary. As a result of the analyzes made, 12 basic quality dimensions, namely performance, usability, durability, reliability, services, price, aesthetics, functionality, perceived quality, safety, environmentalism and conformity, and 35 sub-dimensions under these dimensions were defined. The most evaluated products were mobile phones, computers and televisions, respectively, while the most evaluated brands were Samsung, iPhone and Arçelik. In the evaluations made according to gender, while the dimensions of price, perceived quality, durability, aesthetics, conformity and environmentalism are proportionally evaluated more by men, the rates of women's evaluations in other dimensions are higher.

Bu çalışmanın temel amacı, elektrikli ve elektronik tüketici ürünlerinde müşterilerin kalite algısını belirleyen unsurların doğrudan onların kendi söylevlerinden hareketle belirlenmesidir. Bu amaçla, katılımcılardan kullandıkları ürünlerle ilgili olarak neden kaliteli ve neden kalitesiz olduğunu düşündüklerini maddeler halinde yazmaları istenmiştir. 191 katılımcının anket verilerinin değerlendirmeye tabi tutulduğu çalışmada veriler MAXQDA 2022 programında analiz edilmiştir. Katılımcı ifadelerinin kalite boyutu olarak kodlanmasında öncelikli olarak literatürde yer alan boyutlar dikkate alınmış, gerek görülen yerlerde kalite boyutları altında alt kodlamalara da yer verilmiştir. Yapılan analizler neticesinde performans, kullanışlılık, dayanıklılık, güvenilirlik, hizmetler, fiyat, estetik, fonksiyonellik, algılanan kalite, güvenlik, çevrecilik ve uygunluk olmak üzere 12 temel kalite boyutu ve bu boyutlar altında 35 alt boyut tanımlanmıştır. En çok değerlendirilen ürünler sırasıyla cep telefonu, bilgisayar ve televizyon, en çok değerlendirilen markalar Samsung, iPhone ve Arçelik olmuştur. Cinsiyete göre yapılan değerlendirmelerde fiyat, algılanan kalite, dayanıklılık, estetik, uygunluk ve çevrecilik boyutları oransal olarak erkekler tarafından daha çok değerlendirilmişken diğer boyutlarda kadınların değerlendirmelerine ilişkin oranlar daha yüksektir.
Keywords: Mamul kalitesi; Kalite boyutları; Elektrikli/elektronik ürünler; Metin Kutusu; Product quality; Quality dimensions; Electirical/electronic products; Yöneylem; Operation; 16. Peace & justice